Diagnóstico, diretrizes e desafios para a gestão de resíduos da construção civil no Município de Rio Claro-SP - Lobo, Fernanda Desordi (Universidade Federal de São Carlos, 2011)
A lot of cities have suffered the serious problem about the high volume of waste caused by the civil construction, either in new construction works or in renovation and demolition, concerning with an irreversible phenomenon which is associated with the urban development, the population increasing and the industrialization. The necessity of the minimization of the problems concerned to the environmental, urban and the public health degradation, associated with the bad way the waste is put down and the precariousness of the right conduct, suggests an achievement of some work in this way, having in sight a better life quality for the present and for the future generations. The research will aim at a diagnosis of the waste of the construction work and demolition of the borough of Rio Claro-SP, showing subsidies for the proper management of waste produced, aiming at inquired research of preexisting solutions and producing alternative solutions, which can contribute to a public politics of local productive arrangement in the sector of management of the civil construction waste.
Keywords: Resíduos de construção e demolição; Construção civil; Gestão de resíduos; Impactos sócio-ambientais; Degradação urbana; Degradação ambiental; Gestão adequada; ENGENHARIAS